ANTICOAGULANT THERAPY IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION: DRUG CHOICE AND DOSAGE ADJUSTMENT - E. L. Dolgova; I. M. Sokolov; Yu. G. Shvarts (Рациональная фармакотерапия в кардиологии, 2015)
Data on the problem of thromboembolic complications in non-valvular atrial fibrillation are presented. Peculiarities of anticoagulant therapy to prevent thromboembolic complications, the difficulties in drug choice and dosage adjustment are also discussed.